Influence of Fluid Concentration on the Elevation of Boiling Point of Blackberry Juice - Gabas, A. L.; Sobral, P. J. A.; Cardona-Alzate, C. A.; Telis, V. R. N. [UNESP]; Telis-Romero, J. [UNESP] (Taylor & Francis Inc, 2008)
The rise in boiling point of blackberry juice was experimentally measured at soluble solids concentrations in the range of 9.4 to 58.4Brix and pressures between 4.9 103 and 9.0 104 Pa (abs.). Different approaches to representing experimental data, including the Duhring's rule, a model similar to Antoine equation and other empirical models proposed in the literature were tested. In the range of 9.4 to 33.6Brix, the rise in boiling point was nearly independent of pressure, varying only with juice concentration. Considerable deviations of this behavior began to occur at concentrations higher than 39.1Brix. Experimental data could be best predicted by adjusting an empirical model, which consists of a single equation that takes into account the dependence of rise in boiling point on pressure and concentration.
Keywords: Evaporation; Concentration; Pressure; Blackberry juice